Mn(II) Regulation of Lignin Peroxidases and Manganese-Dependent Peroxidases from Lignin-Degrading White Rot Fungi - Bonnarme, P. (1990)
Two families of peroxidases—lignin peroxidase (LiP) and manganese-dependent lignin peroxidase (MnP)—are formed by the lignin-degrading white rot basidiomycete Phanerochaete chrysosporium and other white rot fungi. Isoenzymes of these enzyme families carry out reactions important to the biodegradation of lignin. This research investigated the regulation of LiP and MnP production by Mn(II). In liquid culture, LiP titers varied as an inverse function of and MnP titers varied as a direct function of the Mn(II) concentration. The extracellular isoenzyme profiles differed radically at low and high Mn(II) levels, whereas other fermentation parameters, including extracellular protein concentrations, the glucose consumption rate, and the accumulation of cell dry weight, did not change significantly with the Mn(II) concentration. In the absence of Mn(II), extracellular LiP isoenzymes predominated, whereas in the presence of Mn(II), MnP isoenzymes were dominant. The release of (14)CO(2) from (14)C-labeled dehydrogenative polymerizate lignin was likewise affected by Mn(II). The rate of (14)CO(2) release increased at low Mn(II) and decreased at high Mn(II) concentrations. This regulatory effect of Mn(II) occurred with five strains of P. chrysosporium, two other species of Phanerochaete, three species of Phlebia, Lentinula edodes, and Phellinus pini.